Rapid detection of Mycoplasma hyopneumoniae by recombinase-aided amplification combined with the CRISPR/Cas12a system - Li, Kaili; Luo, Tingyu; Zhang, Yu; Li, Changwen; Chen, Hongyan; Xia, Changyou; Gao, Caixia (Frontiers in Cellular and Infection Microbiology, 2024)
Mycoplasma hyopneumoniae (M. hyopneumoniae) is one of the primary agents involved in porcine respiratory disease complex, and circulates in the swine industry worldwide. The prevention and control of M. hyopneumoniae is complicated. Thus, a recombinase-aided amplification (RAA) assay coupled with the clustered regularly-interspaced short palindromic repeats (CRISPR)/Cas12a system was established for the detection of M. hyopneumoniae. The most suitable primer pairs and CRISPR RNA (crRNA) were screened and selected for the RAA-CRISPR/Cas12a detection system. We have achieved a detection limit of 1 copy/µL and 5 copies/µL per reaction for the RAA-CRISPR/Cas12a-fluorescence assay and RAA-CRISPR/Cas12a-lateral flow assay (LFA), respectively. Furthermore, the RAA-CRISPR/Cas12a system displayed no cross-reactivity with other respiratory pathogens. The performance of the RAA-CRISPR/Cas12a system was compared with PCR as recommended by the Chinese national standard (GB/T 35909-2018) and qPCR as recommended by the Chinese entry–exit inspection and quarantine industry standard (SN/T4104-2015) for clinical samples, and good consistency with these methods was observed. Above all, the methods shed a light on the convenient, portable, visual, highly sensitive and specific detection of M. hyopneumoniae, demonstrating a great application potential for on-site monitoring of M. hyopneumoniae in the field.